2020
DOI: 10.1111/jfbc.13468
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of oyster peptides and oyster powder on cyclophosphamide‐induced reproductive impairment in male rats: A comparative study

Abstract: In addition to being nutritional elements, proteins in food can also regulate the body's physiological functions, which is achieved via specific peptide sequences in the proteins (Chakrabarti, Guha, & Majumder, 2018). Therefore, although many bioactive peptides are stored in dietary proteins, the peptides remain inactive in the protein sequence and only have specific physiological functions after being released (Kitts & Weiler, 2003). Proteases from various sources can release biologically active peptides (Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The treatment of OPs restored the serum hormone level of mice to the normal, and reduced the disturbance of hormones on spermatogenesis in mice. Additionally, previous studies had found that oyster peptides improved the level of serum androgen induced by cyclophosphamide [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of OPs restored the serum hormone level of mice to the normal, and reduced the disturbance of hormones on spermatogenesis in mice. Additionally, previous studies had found that oyster peptides improved the level of serum androgen induced by cyclophosphamide [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on OPs also revealed that they have collagen-restoring capabilities (i.e., anti-wrinkle properties) ( Hao et al, 2021 ). Further, OPs promote sexual reproduction by increasing the expression of key regulatory proteins and androgens, thereby increasing serum estrogen levels and improving male sexual function ( Li et al, 2020 ). For instance, GnRH-like peptides (Cg-GnRH-a and Cg-GnRH-G) isolated from the visceral ganglion of oysters regulate neurological and endocrine factors and provide nutrition and energy for reproduction ( Bigot et al, 2012 ).…”
Section: Oyster Tissuesmentioning
confidence: 99%
“…100 GnRH-like peptides were first isolated from 101 and have been proposed to exist in bivalve molluscs 102 Moreover, GnRH II has been found to regulate nutritional status and reproductive ability in vertebrates. 103 Oyster peptides have a demonstrated role in promoting reproduction by effectively increasing the expression of key regulatory proteins in the androgen production pathway, 4 which leads to higher serum testosterone levels and enhanced male sexual function. In a previous study with normal male mice fed with alkaline protease hydrolysate of oyster, mount latency (ML) decreased, whereas ejaculatory latency (EL), mount frequency (MF) and ejaculation frequency (EF) increased.…”
Section: Sexual Reproduction Promoting Activitymentioning
confidence: 99%